2018
DOI: 10.20396/parc.v9i1.8650725
|View full text |Cite
|
Sign up to set email alerts
|

Iluminação natural em edifícios de escritórios: avaliação dinâmica de desempenho para São Paulo

Abstract: A revisão dos critérios definidores de conforto visual e o teste de novos métodos de avaliação da iluminação natural de edifícios, com base no clima, vem sendo realizados na última década. Nesse contexto, o principal objetivo deste trabalho é analisar o desempenho da luz natural em um edifício de escritórios de planta profunda representativo da produção recente na cidade de São Paulo, por meio de simulações dinâmicas com base em dados climáticos para a definição da zona passiva de iluminação natural em diferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…This solution of highly glazed façades has been replicated in large cities, such as Sao Paulo, Belo Horizonte, and Brasilia. Studies reported problems related to glare, excess light on working surfaces, and an increase in energy consumption for lighting due to the incidence of direct sunlight inside the working environment [25][26][27][28][29]. Moreover, the use of clear glass was also identified on facades in Brasilia and Sao Paulo in modernist buildings, mostly built between the 1960s and 1970s [24,27,30].…”
Section: Glazed Façades: Brazilian Context Of Non-residential Buildin...mentioning
confidence: 99%
See 1 more Smart Citation
“…This solution of highly glazed façades has been replicated in large cities, such as Sao Paulo, Belo Horizonte, and Brasilia. Studies reported problems related to glare, excess light on working surfaces, and an increase in energy consumption for lighting due to the incidence of direct sunlight inside the working environment [25][26][27][28][29]. Moreover, the use of clear glass was also identified on facades in Brasilia and Sao Paulo in modernist buildings, mostly built between the 1960s and 1970s [24,27,30].…”
Section: Glazed Façades: Brazilian Context Of Non-residential Buildin...mentioning
confidence: 99%
“…7. This model represented a generic office space within the Brazilian context, and its dimensions were based on the studies of Amorim et al [50], Cavaleri, Cunha, and Gonçalves [26], and Sarra and Mühlfart [27]. The walls, floor, and roof were modeled using the command "box," inserting the already described dimensions, with a width of 0.15 m. The surfaces corresponding to the floor, ceiling, and window were modeled using the command "_SrfPt.…”
Section: Simulation Model Parameters and Variablesmentioning
confidence: 99%
“…The windowto-wall ratio varied from 40%, the minimum aperture allowed by local laws (Santa Maria, 2018), to 100%, in 10% increments Tinker, 2001). The UDI-autonomous (500-2,500 lx) was adopted with a range between 0 to 500 lx taken as the short range, 500 to 2,500 lx as the desirable range, and illuminance more than 2,500 lx as the oversupply (Asfour, 2020;Marcondes Cavaleri;Gonçalves, 2018;Fernandes;Ruivo;Krebs, 2018;Heschong;Lee, 2009;Qiu;Yang, 2020;Queiroz;Westphal;Pereira, 2020). The DA (500 lx) was based on the Brazilian standard that determines the minimum level considering activities such as medical service; reading and writing; computer-aided design, among others, which are everyday tasks developed in offices (ABNT, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Calama-González, Suárez e León-Rodriguez (2018) estudaram o uso de dispositivos de proteção solar como forma de redução do consumo com iluminação e ar-condicionado em edificações escolares e observaram uma redução de cerca de 20% no consumo com ar-condicionado e 50% no consumo com iluminação artificial. Percebe-se, a partir de pesquisas realizadas por diversos autores, que o uso correto de protetores solares, a aplicação de propriedades ópticas adequadas em fachadas de edifícios, controles da iluminação artificial, além de outros parâmetros, resultam em melhor desempenho energético da edificação, assim como maior conforto aos usuários (CRUZ E SILVA, 2011;DIDONÉ;PEREIRA, 2010;MELLO, 2019;LAZZARIS;CARVALHO;GALAFASSI, 2019;QUEIROZ;PEREIRA, 2019;MARCONDES CAVALERI;CUNHA;GONÇALVES, 2018;OUAHRAMI;TOUMA et al, 2016).…”
Section: Introductionunclassified